ANALISIS TERHADAP USAHA MENDAULATKAN DINAR DAN DIRHAM SEBAGAI MATA WANG ALTERNATIF DUNIA ISLAM - Abd Majid, M. Shabri (Jurnal Syariah, 2006)
This paper highlights the supremacy of Islamic gold dinar and silver dirham over the current paper money (fiat money). Many contemporary Islamic economists believe that dinar and dirham are a desirable alternative of money viewed from social, economic, politic and religious perpectives. The paper then focuses on both prospects and challenges faced by Muslim countries in their efforts to return to dinar and dirham. At the initial stage of implementating dinar and dirham, the current fiat money, dinar and dirham may coexist while a transition takes place gradually. The gradual implementation of dinar and dirham is aimed at avoiding shock to the economy. In addition, the Muslim efforts to return to dinar and dirham will be eased by the advancement of Information and Communication Technology (ICT). The paper finally discusses the transaction models of dinar and dirham. From these transaction models, it is found that a small bushel of the gold can support a large number of international transactions. Therefore, the shortage of gold and silver on this earth is not an impediment for Muslims to return to dinar and dirham as their alternative currency.